2023
DOI: 10.1021/acs.chemmater.2c03226
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Nucleation and Growth of Pd Nanocrystals from Aqueous Solution Studied by In Situ Liquid Transmission Electron Microscopy

Abstract: Direct visualization and understanding of the atomic mechanisms governing the growth of nanomaterials are crucial for designing synthesis strategies of high specificity. Aside from playing a key role in numerous technological applications, palladium clusters and nanoparticles are particularly valuable due to their outstanding catalytic activity. Studies show that the properties of Pd nanomaterials depend on shape and size. Therefore, optimizing the synthesis to control the final size and shape of Pd nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Erni and co-workers investigated nanoparticle coalescencebased growth mechanisms using GLC-TEM to visualize nanoparticle formation at the atomic scale. 33,[97][98][99][100] They observed that metal atom aggregation into metal clusters played a vital role in facilitating attachment-based growth of PtPd nanoparticles (Fig. 5f).…”
Section: Formation Mechanism and Dynamics Of High Entropy Alloy Nanop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Erni and co-workers investigated nanoparticle coalescencebased growth mechanisms using GLC-TEM to visualize nanoparticle formation at the atomic scale. 33,[97][98][99][100] They observed that metal atom aggregation into metal clusters played a vital role in facilitating attachment-based growth of PtPd nanoparticles (Fig. 5f).…”
Section: Formation Mechanism and Dynamics Of High Entropy Alloy Nanop...mentioning
confidence: 99%
“…5g. 100 Initially, Pd atom aggregation formed amorphous metal clusters, which continuously aggregated and coalesced to form large amorphous particles. Finally, the amorphous particles crystallized with defined facets.…”
Section: Formation Mechanism and Dynamics Of High Entropy Alloy Nanop...mentioning
confidence: 99%
“…The study of Pt nanoparticles using LC-TEM has inspired the study of other noble metal particles, including Au, [58][59][60][61] Ag, 62,63 and Pd 64 and their nano-alloy. [65][66][67] Zhu et al 68 found that the nucleation and growth of Au nanoparticles in a mixed solution of 34 mM sodium citrate and 0.24 mM HAuCl 4 had the same mechanism, and noticed that the agglomeration of particles was preferred on {111} planes due to the lower ligand binding energy.…”
Section: Liquid-cell Tem For Liquid-phase Synthesismentioning
confidence: 99%
“…Two technological approaches are used: self-propagating synthesis and volumetric combustion synthesis. The methodology of the first one provides for the mechanism of spontaneous redox endothermic reactions between the oxidiser and the fuel, which are mixed at the molecular level in the corresponding solution with the gradual establishment of the target product in the solid aggregate state [33]. The second technological approach involves external heat supply to the entire volume of the reagent solution.…”
Section: Graphical Representation Of the Process Brief Description Of...mentioning
confidence: 99%